Impact of Cooling Air Temperature and Airflow on Wood Fuel Pellet Durability, Hardness, and Off-Gassing During Industrial Storage - Magnus Ståhl; Jonas Berghel (BioResources)
The cooling of pellets is necessary because pellets reach 70 to 90 °C after the pellet press. The reduction in temperature solidifies the pellets, which increases the pellet quality and reduces the risk of self-heating during storage. Industrially, pellet plants use outdoor air in counterflow coolers and cooling ends when the pellet temperature is approximately 5 °C above ambient temperature. Cooling performed in the summer could result in high temperatures in the pellet stacks during storage, and cooling at low temperatures and high airflows in the winter could cause quality problems. Therefore, the aim was to determine how cooling air temperature, airflow, and storage time impact the durability, hardness, and off-gassing of the pellets. The results showed that the highest durability (97.7%) and hardness (310 N) were achieved when cooling with low-temperature air and low airflow. Additionally, durability and hardness stabilized at high values (98.9% and 640 N) after 30 to 40 days of storage, regardless of the airflow and cooling air temperature used. Furthermore, it was found that high airflows reduce off-gassing regardless of the cooling air temperature. It is recommended that the industry reduce airflow during the winter and increase it during the summer to produce high-quality pellets and minimize the risk of self-heating.